Doctors' experience of the contraceptive consultation: a qualitative study in Australia. Issue 2 (12th May 2016) - Kelly, Marguerite; Inoue, Kumiyo; Black, Kirsten I; Barratt, Alexandra; Bateson, Deborah; Rutherford, Alison; Stewart, Mary; Richters, Juliet
Abstract : Background: Contraception is a field in which good doctor–patient communication is crucial and core to shared decision making. Despite the centrality of contraception to primary health care in Australia, little is known about how doctors manage the contraceptive consultation. In particular, little is known about how doctors discuss sexual issues related to contraception. Methods: Fifteen contraceptive providers participated in qualitative interviews averaging 45 min. Interviews were audio recorded, transcribed verbatim, and analysed using an inductive thematic approach. Results: We found doctors were aware that they had to modify their illness-based 'scripts' in consultations about contraception, and said it was challenging always to adhere to a shared model of decision making. Prescribing behaviour reflected personal preferences in relation to some forms of contraception, and doctors were enthusiastic about the levonorgestrel-releasing intrauterine system. Doctors identified gaps in training in relation to sexuality and reported feeling tentative in raising sexual issues, even within contraceptive consultations. Conclusions: A range of factors—including tendencies to use illness scripts, personal preferences, and discomfort with communications about sexuality—appear to influence doctors' approaches to contraceptive management. Medical training that enables doctors to move out of an illness-treating framework and to improve their understanding of and comfort in discussing sexuality issues will improve their management of healthy women seeking contraception.